(untitled) (Development Service Industry Management, 2024)
This article is dedicated to examining potential directions for developing the investment potential of enterprises in the tourism sector. The article aims to enhance the existing theoretical and methodological framework for the functioning of a company’s investment potential and to develop a comprehensive approach that includes directions for investment potential development within tourism enterprises. The article considers the investment potential of tourism sector enterprises as a multifaceted concept encompassing financial, material, human, organizational, and other resources. The study highlights key aspects of investment potential that facilitate investor attraction, infrastructure development, and the adoption of innovations in the tourism industry. It substantiates the importance of financial capacity for compelling investment attraction, emphasizing that access to financial resources through banks, investment funds, and venture capital is essential for developing tourism enterprises. The main components of investment potential are presented, including human resources, material and technical base, innovative technologies, ecological and social aspects, and political and legal stability. It is shown that well-developed infrastructure, including hotels, transport networks, and other facilities, enables enterprises to attract investors and provide comfort for tourists. The research emphasizes the importance of human resources, as qualified personnel are a critical element for the effective implementation of tourism projects. The study also highlights the significance of innovative technologies, such as information and communication systems for online booking, the adoption of green technologies, and the automation of management processes. Enterprises’ ecological and social responsibility is another important aspect that enhances attractiveness for investors focused on sustainable development. Political stability and legal protection of investments are underscored as vital for creating a favorable investment climate. The investment potential of tourism sector enterprises is viewed as a multifaceted mechanism integrating financial, human, innovative, ecological, and legal factors. The effective use of these components promotes the industry’s sustainable development and ensures the competitiveness of tourism enterprises.